Analisis Kualitas Air Sungai Palopo Akibat Pencemaran Limbah Domestik Dengan Metode Index Pollution: Analysis of Palopo River Water Quality Due to Domestic Waste Using the Index Pollution Method - KHAERUL AMRU; BUKROANAH AMIR MAKKAU (Jurnal Teknologi Lingkungan, 2023)
The rapid population growth in Palopo City has caused human activities to increase which has an impact on environmental pollution, especially river pollution due to domestic wastewater disposal. This study aims to determine the condition of water quality in the Palopo River considering the enormous pollution from domestic waste disposal. The research location was carried out along the Palopo River which is located in Palopo City, South Sulawesi. The methods used include survey methods with samples taken using Purposive techniques. Determination of the quality of water is calculated using the Pollution Index method with the parameters TSS, TDS, COD, BOD, ammonia, and total coliform. Based on the results of the Pollution Index analysis, it shows that the river waters located at sample point 1 which is located in the upper reaches of the river are in a lightly polluted quality status with an IP value of 3.28. Whereas for sample points 2, 3, and 4 which are located in the middle part of the river, they are included in the status of moderately polluted water quality with an IP value of 6.19; 6.21; and 6.19. Meanwhile point 5 which is located in the lower reaches of the river is included in the status of moderately polluted water quality with an IP value of 6.27. ABSTRAK Pertumbuhan penduduk yang begitu pesat di Kota Palopo menyebabkan aktivitas manusia meningkat yang berdampak terhadap pencemaran lingkungan khususnya pencenaran sungai akibat pembuangan air limbah domestik. Penelitian ini bertujuan untuk mengetahui kondisi kualitas air di Sungai Palopo mengingat pencemaran dari pembuangan limbah domestik yang sangat besar. Lokasi penelitian dilakukan di sepanjang Sungai Palopo yang berlokasi di Kota Palopo Sulawesi Selatan. Metode yang digunakan meliputi metode survey dengan sampel diambil menggunakan teknik Purposive. Penentuan kualitas mutu air dihitung menggunakan metode Indeks Pencemaran (Index Pollution) dengan parameter TSS, TDS, COD, BOD, amoniak, dan total coliform. Berdasarkan hasil analisis Indeks Pencemaran menunjukkan bahwa perairan sungai yang berada pada lokasi titik sampel 1 yang terletak di bagian hulu sungai berada pada status mutu tercemar ringan dengan nilai IP sebesar 3,28. Sedangkan untuk titik sampel 2,3, dan 4 yang terletak pada penggalan sungai bagian tengah termasuk ke dalam status mutu air tercemar sedang dengan nilai IP 6,19; 6,21; dan 6,19. Sementara untuk titik 5 yang terletak di bagian hilir sungai masuk ke dalam status mutu air tercemar sedang dengan nilai IP 6,27.